Protease Activated Receptor 1 and Its Ligands as Main Regulators of the Regeneration of Peripheral Nerves - Elena Pompili; Valerio De Franchis; Claudia Giampietri; Stefano Leone; Elena De Santis; Francesco Fornai; Lorenzo Fumagalli; Cinzia Fabrizi (Biomolecules, 2021)
In contrast with the brain and spinal cord, peripheral nerves possess a striking ability to regenerate after damage. This characteristic of the peripheral nervous system is mainly due to a specific population of glial cells, the Schwann cells. Schwann cells promptly activate after nerve injury, dedifferentiate assuming a repair phenotype, and assist axon regrowth. In general, tissue injury determines the release of a variety of proteases which, in parallel with the degradation of their specific targets, also activate plasma membrane receptors known as protease-activated receptors (PARs). PAR1, the prototypical member of the PAR family, is also known as thrombin receptor and is present at the Schwann cell plasma membrane. This receptor is emerging as a possible regulator of the pro-regenerative capacity of Schwann cells. Here, we summarize the most recent literature data describing the possible contribution of PAR1 and PAR1-activating proteases in regulating the regeneration of peripheral nerves.